INDICADORES BIOQUÍMICOS E ANTROPOMÉTRICOSCOMO PREDITORES DE SÍNDROME METABÓLICA EM ESTUDANTES UNIVERSITÁRIOS - LIMA, Alice Marques Moreira (2020)
Metabolic Syndrome (MetS) is defined as a complex disorder associated with cardiovascular risks and caused by clinical conditions, which can contribute to the development of atherosclerosis, hypertension and diabetes mellitus II.Although there is evidence of the impact of MS on the health of the young population, there are few studies related to the identification of the prevalence of this clinical condition in specific groups. The aim of this work was to associate biochemical and anthropometric indicators as predictors of MS in students at a public university in Northeast Brazil. A quantitative approach was used in a cross-sectional, observational, descriptive study with university students. The characterization of MS was performed according to diagnostic criteria of the Harmonized Joint Scientific Statement (HJSS), where the participants who presented three or more of the variables blood pressure (BP), waist circumference (WC), glycemia (GL), triglyceride (TG), altered low density lipoprotein (HDL) were classified as positive for MetS. To assess possible associations between variables, statistical analysis was performed using odds ratio (OR), with 95% confidence intervals, with a 5% significance level and logistic regression analysis.The results show that 7.99% of the students were classified with MetS. The prevalence of men with MetS was 12.07% and women 5.86%.The association between the metabolic syndrome and sex was verified (χ2 = 4.00; p = 0.04), and that males were 2.2 times more likely to present the outcome in the 95% confidence interval (1 , 01 - 4.87). The triad of variables most present in women was WC> HDL> TG with increased abdominal circumference (27.48%), decreased HDL (18.92%), hypertriglyceridemia (11.26%), while in men, it was HDL> BP > WC, with HDL decreased (39.66%), altered blood pressure (31.90%) and increased abdominal circumference (25.00%). Regarding lifestyle, the sedentary were (48.22%), alcohol users (48.82%) and smokers (10.36%), however despite the prevalence, they did not present significant values. With the regression analysis, it was possible to identify individuals who have altered WC have up to 29.7 times more chance to develop MetS, HDL decreased up to 21.76 times, BP increased up to 18 times, hypertriglyceridemia up to 25 times and hyperglycemia up to 21.4 times. Thus, it is possible to perceive the severity when three or more of these associated components are present in determining MetS. HDL and WC are present in both sexes as significant risk factors for MetS, which deserves attention.Therefore, the prevalence of MetS in populations should be monitored, as the expansion of this Syndrome in Brazil and in the world, can lead to an increase in cardiovascular and metabolic diseases with several complications.